Carbon-based dots for the electrochemical production of hydrogen peroxide. Issue 55 (9th June 2020) - Dong, Yongqiang; Su, Juanxia; Zhou, Shuqing; Wang, Min; Huang, Shuping; Lu, Chun-Hua; Yang, Hongbin; Fu, Fengfu
Abstract : Graphene/carbon-based dot nanohybrids were prepared by the ultrasonic exfoliation of natural graphite in the presence of single-layer carbon based dots, and used for the electrochemical production of hydrogen peroxide. Abstract : In this study, natural graphite was liquid exfoliated in the presence of single-layer carbon-based dots (CDs), which were used as intercalators. It was found that graphene of mainly single-layer has been obtained, on which lots of CDs were deposited. Combining the unique properties of these two materials, the CDs deposited on graphene (G/CDs) are proved to be outstanding catalysts for the electroreduction of oxygen to H2 O2 . The results from control experiments and density functional theory calculations demonstrated that the oxygen-containing functional groups on the CDs played a key role in the catalytic activity of the G/CDs.